Potential impact of the sea-ice ecosystem to the polar seas biogeochemistry - Kwon, Young Shin; Rhee, Tae Siek; Bolding, Karsten (Frontiers in Marine Science, 2023)
We used a one-dimensional vertical transport model, the sympagic-pelagic-benthic vertical transport model (SPBM) to explore the impact of sea-ice presence on phytoplankton phenology and biogeochemical dynamics. In the model, we introduced new parameter values for sympagic diatoms using ERSEM (European Regional Seas Ecosystem Model) in addition to the existing phytoplankton groups in the sea-ice model. We found that different groups of primary producers exhibit distinct spatial and temporal variabilities in both the sea-ice and water column depending on their physiological and biogeochemical properties. In particular, we discovered that the biomass of pelagic diatoms during the bloom season is strongly influenced by the release of sympagic algal cells during the early spring. This suggests the potential significance of sympagic algae seeding for the occurrence of pelagic diatom blooms in the Amundsen Sea. Notably, our model also indicates a potential connection between the earlier peak in particulate organic carbon flux and the release of sympagic-algae-associated particles from the sea ice, followed by their rapid sinking. Previous studies relying solely on observational data did not fully account for this mechanism. Our findings emphasize the importance of understanding the role of sympagic algae in the polar ecosystem and carbon cycle, and shed light on the complex biogeochemical dynamics associated with the sea-ice ecosystem in the polar seas.